Unbreakable Kimmy Schmidt. Season one [videorecording (DVD)] - Fey, Tina, 1970- (Universal Studios Home Entertainment, 2016)
Rescued after fifteen years in an underground doomsday cult, Kimmy decides to rebuild her life in New York City armed with only a fifth-grade education and a firm belief that truly anything is possible. She quickly finds a roommate, Titus Andromedon, a job working for a spoiled Manhattan mom, Jacqueline Voorhees, and a new beginning.